2018
DOI: 10.20945/2359-3997000000020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of historic histopathologic sample review on the risk of recurrence in patients with differentiated thyroid cancer

Abstract: Objective: To compare the historic risk of recurrence (RR) and response to therapy to risk stratification estimated with historical pathology reports (HPRs) and contemporary re-review of the pathological slides in patients with differentiated thyroid cancer (DTC). Subjects and methods: Out of 210 DTC patients with low and intermediate RR who underwent total thyroidectomy and remnant ablation in our hospital, 63 available historic pathologic samples (HPS) were reviewed. The RR and the response to therapy were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…I read with great interest the recently published manuscript in Endocrine from Hescot et al [1] in which they report similar results to what we had already reported in 2018 [2].…”
supporting
confidence: 83%
“…I read with great interest the recently published manuscript in Endocrine from Hescot et al [1] in which they report similar results to what we had already reported in 2018 [2].…”
supporting
confidence: 83%
“…The Modified Stratification System from ATA 2009 guidelines was also validated in several cohorts of patients around the world (Pitoia et al 2015, Momesso et al 2016, Abelleira et al 2017, Park et al 2017. In an investigation performed in 63 patients with low and intermediate RR from our hospital, we concluded that additional histopathological variables proposed by this new stratification system allowed for a greater refinement in the prediction of the different responses to treatment (Pitoia et al 2018).…”
Section: Introductionmentioning
confidence: 84%
“…Ganly et al 11 with similar follow-up and without ablative doses had not recorded recurrent events. Recently, Pitoia et al 12 Have we overtreated patients with NIFTP? It is important to remember that these tumors were treated as carcinomas according to the current protocol (surgery and subsequent ablation in most cases).…”
Section: Discussionmentioning
confidence: 99%